La reglamentación de la vida sexual en el islam: interferencia y fusión entre derecho y sexualidad - Torres Calzada, Katjia (Ambigua: Revista de Investigaciones sobre Género y Estudios Culturales, 2014)
Abstract: This article deals with the interference of Islamic law in sexuality and merging in existing criminal codes of the Islamic Arab states. Analyzing the legal texts regulating sexuality in Arab-Islamic countries: Islamic canon law, its main sources - The Qur'ān and the sunna - and existing criminal codes, it is found that the criminal sanction considered illicit sexual practices (zinā) promotes the restoration, today, two types of criminal offenses under a category medieval (ḥudūd), which are sex outside marriage and homosexuality, around which turns our study. Analyzing the legal texts regulating sexuality in Arab-Islamic countries: Islamic canon law, its main sources - The Qur'ān and the sunna - and existing criminal codes, it is found that the criminal sanction considered illicit sexual practices (zinā) promotes the restoration, today, two types of criminal offenses under a category medieval (ḥudūd), which are sex outside marriage and homosexuality, around which turns our study. From this analysis it is concluded that the interference of Islamic law favors a two-speed sexuality in the light of court rulings in recent years in several Arab-Islamic countries, whose function requires no visible deterrent such practices. We address briefly the origin, evolution of Islamic law and its penal code. Next, try pairing this encoding with sex outside of marriage and homosexuality through the articles that sanction these practices. To understand the significance of this measure, we make an approximation of the concept of sexuality, desire and sexual freedom contained in the sources of Islamic law and Islamic law the main treaties, from the beginning of the implementation of the sharia to our days. We conclude by treating the deterrent function of penalizing these practices, which is none other than promoting sexuality at two speeds: one that requires religion and morality and society lives. Key words: Islam; šarī῾a; criminal code; sexual freedom; LGBT. Resumen: El presente artículo trata la interferencia del derecho islámico en la sexualidad y su fusión en los vigentes códigos penales de los Estados árabes islámicos. Analizando los textos legales que regulan la sexualidad en los países árabo-islámicos: ley canónica islámica, sus fuentes principales –El Corán y la sunna– y los códigos penales vigentes se comprueba que la sanción penal de las prácticas sexuales consideradas ilícitas (zinā) propicia la reinstauración, hoy día, de dos tipos de delitos bajo una categoría penal medieval (ḥudūd), que son el sexo fuera del matrimonio y la homosexualidad, en torno a la cual gira nuestro estudio. De dicho análisis se concluye que la interferencia del derecho islámico propicia una sexualidad a dos velocidades, a la luz de las sentencias judiciales dictadas en los últimos años en varios países árabo-islámicos, cuya función disuasoria obliga a no visibilizar estas prácticas. Abordamos el origen, evolución del derecho islámico y su codificación penal. Seguidamente, tratamos la vinculación de esta codificación con el sexo fuera del matrimonio y la homosexualidad, a través de los artículos que sancionan estas prácticas. Para comprender la transcendencia de esta medida, nos aproximamos a la concepción de la sexualidad, el deseo y libertad sexuales recogida en las fuentes del derecho islámico y los principales tratados jurídicos islámicos, desde el comienzo de la aplicación de la šarī῾a hasta nuestros días. Concluimos tratando la función disuasoria de la penalización de estas prácticas, que no es otra que el propiciar una sexualidad a dos velocidades: la que exige la religión y la moral y la que vive la sociedad. Palabras clave: Islam; šarī῾a; código penal; libertad sexual; LGBT.